A discrete time deteriorating inventory system with geometric lead time. (1st January 2013) - Lawrence, A. Shophia; Sivakumar, B.; Arivarignan, G.
A discrete time ( s, S ) inventory system with demands occurring according to a Bernoulli process and geometrically distributed lead time is considered in this work. We address the situation in which the perishable items are packaged and stored in a suitable and controlled environment so that items in the packets do not perish over time. However, when a packet is opened to meet a unit demand, we assume that all the remaining items of that packet, which are brought out of controlled environment, may start decaying. As ( s, S ) type ordering policy is adopted for the packets. The distribution of the inventory level is obtained in the steady state. The system performance measures are derived and the results are illustrated numerically.